VISION OF THE GAS PRODUCTION SECTOR DEVELOPMENT IN UKRAINE - Перевозова, Ірина Володимирівна; Гринів, Петро Михайлович (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2022)
The current state, problems and prospects of the gas production sector development in Ukraine are analyzed. Based on the works of domestic scientists, a study of the fuel and energy complex as a whole was conducted. The main trends, natural gas producers and consumers by functional and regional characteristics are highlighted. Attention was focused on the need to ensure Ukraine’s economic and energy security in the gas sector. The purpose of the article is a mechanism for improving the justification of the vision of the development of enterprises in the gas production sector of Ukraine, from the point of view of the need to ensure the country’s energy independence and energy efficiency. In order to form a vision for enterprise development in the gas production sector, a study of the economic statistics indicators system was conducted. A retrospective analysis of the energy balance of Ukraine during 2016-2020 was also carried out. The priority role of the gas sector in the supply of primary energy for the needs of the economy was clarified. An assessment of the own production of natural gas and dependence on imports was made. It has been proven that the problem of enterprise development in the gas production sector in Ukraine should be considered in conjunction with the implementation of energy efficiency and resource-saving measures. It is substantiated that reserves for reducing natural gas consumption are the use of biofuel and waste at the intermediate use stage and at the final use stage – savings in heavy industry and households. The scientific novelty of the work was formed, which consists in improving the mechanism for substantiating the vision of enterprise development in the gas production sector of Ukraine on the basis of an interrelated indicators system of economic statistics, which, unlike the existing ones, is based on retrospective data of the consolidated energy balance and allows decisions to be made regarding reserves for the growth of gas energy independence and energy efficiency.